THE EFFECTS OF SYMMETRICAL AND ASYMMETRICAL SCAFFOLDING ON SPEAKING COMPLEXITY, ACCURACY, AND FLUENCY - Parviz Ghasedi; Farideh Okati; Habibollah Mashhady; Nasser Fallah (Indonesian EFL Journal, 2018)
This experimental study was set ought to explore the efficacy of symmetrical and asymmetrical scaffolding in boosting speaking complexity, accuracy, and fluency among 38 upper-intermediate EFL learners. To this end, the participants were assigned into random, homogeneous, and heterogeneous groups. The control group participated in normal speaking classroom, while the experimental groups shared their ideas and collaboratively complete tasks related to 7 lessons of New Interchange 2 during 15 sessions. Two different versions of IELTS speaking test were used as pre/post-test. The data were audio recorded and transcribed for statistical analysis. The results of Multivariate tests revealed that there was a statistically significant difference between the mean scores of control and experimental groups on complexity and fluency. On the other hand, descriptive statistics showed the superiority of heterogeneous groups over homogeneous ones. However, the results of Independent sample t-test indicated that the differences between homogeneous and heterogeneous groups reached the significant level just for complexity not fluency and accuracy. Briefly, the results lead support to the Vegotsky’s (1978) socio-cultural theory. The findings and pedagogical implications were discussed in details at the end of the study.Keywords: accuracy, asymmetrical scaffolding, complexity, fluency, symmetrical scaffolding